2022
DOI: 10.1002/cam4.4536
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid silences CYP19A1/aromatase to suppress gastric cancer growth

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The CYP19A1 gene exhibits polymorphism and mutations, which can alter its expression or aromatase activity, consequently impacting the overaccumulation of estrogen and cancer progression . In a study by Ma et al, it was found that CYP19A1 (cytochrome P450 family 19A1; also known as aromatase, Ar) is associated with GCa prognosis . Taxifolin partly exerts an antigastric cancer effect by inhibiting the AhR/CYP1A1 signaling pathway .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CYP19A1 gene exhibits polymorphism and mutations, which can alter its expression or aromatase activity, consequently impacting the overaccumulation of estrogen and cancer progression . In a study by Ma et al, it was found that CYP19A1 (cytochrome P450 family 19A1; also known as aromatase, Ar) is associated with GCa prognosis . Taxifolin partly exerts an antigastric cancer effect by inhibiting the AhR/CYP1A1 signaling pathway .…”
Section: Resultsmentioning
confidence: 99%
“…41 In a study by Ma et al, it was found that CYP19A1 (cytochrome P450 family 19A1; also known as aromatase, Ar) is associated with GCa prognosis. 42 Taxifolin partly exerts an antigastric cancer effect by inhibiting the AhR/CYP1A1 signaling pathway. 43 The FNDC1 gene, located on human chromosome 6q25.3, acts as a G-protein signaling-independent activator and activates G-protein signaling by interacting with Gβγ subunits.…”
Section: Boll Has Been Identified As a Key Rbp Involved In The Growth...mentioning
confidence: 99%
“…Phytochemicals including UA may exert powerful efficacy against a variety of malignancies, such as CRC, gastric cancer, breast cancer, prostate cancer, , and lung cancer, with fewer adverse reactions in comparison with the compounds of chemotherapy, which gives rise to broad utilization of phytochemicals as nutraceuticals for intervention in various cancers. However, the action mechanisms for most phytochemicals remain to be clarified, and UA is one of them in great need of exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Heat-clearing and detoxifying properties of traditional Chinese, including Hedyotis diffusa, Oldenlandia diffusa, Prunella vulgaris, Scutellaria barbata, and Ligustrum lucidum, have shown signi cant e cacy in the treatment of CRC. These herbal medicines have been reported to promote tumor cell apoptosis, reverse multidrug resistance, and inhibit tumor angiogenesis [37][38][39]. However, the speci c mechanisms and targets of these herbal medicines require further investigation.…”
Section: Discussionmentioning
confidence: 99%